MHC IMMUNOGENETICS INFLUENCES THE REPRODUCTION IN SHEEP - MIR, MANZOOR R; GELDERMANN, H; WANl, G M (The Indian Journal of Animal Reproduction, 2023)
Experiment was conducted in four consecutive lambings to establish feta-maternal immune response in a sheep flock of 639 animals. A total of 16 DRB1 microsatellite alleles3 , ranging between 353 and 857 bp were detected which were associated with variable reproductive performances among males and females. Ewes carrying 411 bp allele exhibited higher values for all recorded fertility traits (p<0.001 ), followed by 386 bp allele whereas 389 bp allele had negative values in all fertility traits. The associations of different alleles with variable reproductive traits in sheep could be individual variability to humoral immune response, cell recognition or tissue differentiation between carriers of various MHC genotypes. The observed associations within DRB1 microsatellite locus of Ovine MHC in German Merino sheep may be used as a molecular marker for identifying QTL in genetic improvement of the sheep and also quantifying the MHC lmmunogenetic influences in the reproduction in sheep.